Pengaruh Program Pelatihan dan Pengembangan Guru terhadap Kualitas Pelayanan Prima Sekolah di Indonesia - Nunti Sibuea (STKIP PGRI SITUBONDO, 2023)
The purpose of this study is to determine the extent to which the behavioral variables of teacher training and development in Indonesia, both partially and simultaneously affect the quality of excellent school services throughout Indonesia through competency improvement variables as intervening variables. The population of this study is teachers throughout Indonesia which amounts to 1,485,602 people and the sampling method in this study is to use the accidental sampling method, where the number of samples that exist after being calculated using the slovin formula is 400 teachers throughout Indonesia. The data analysis used is to use quantitative descriptive methods using structural equation model (SEM) analysis. The results of the study explained that partially the variables of training and development of school teachers in Indonesia affect the variables of the quality of excellent service in schools in Indonesia and these two variables affect the variables of increasing teacher competence in Indonesia, Simultaneously, the variables of training and development of school teachers in Indonesia affect the variables of excellent service quality of schools in Indonesia through the variable of increasing teacher competence as an intervening variable, where with the increase in teacher training and professional development, it is hoped that teachers will be able to hone and sharpen their abilities and skills, especially their competence in improving the ability to teach and learning process consistently and continuously, so that later students will increase their abilities and knowledge to be useful for the community.